Peripheral Resistance Baroreflex During Incremental Bicycle Ergometer Exercise: Characterization and Correlation With Cardiac Baroreflex - Porta, Alberto; Bari, Vlasta; Maria, Beatrice De; Cairo, Beatrice; Vaini, Emanuele; Malacarne, Mara; Pagani, Massimo; Lucini, Daniela (Frontiers in Physiology, 2018)
The arm of the baroreflex (BR) controlling peripheral resistances (PR), labeled as prBR, was characterized through an extension of the cardiac BR (cBR) sequence analysis. The method exploits recordings of skin blood flow (SBF) from the palm of the nondominant hand via a laser Doppler flowmeter and of arterial pressure (AP) from the middle finger of the same hand via a plethysmographic device. PR was estimated beat-by-beat as the ratio of mean AP to mean SBF computed over the same heart period (HP). PR-DAP patterns featuring simultaneous increases of PR and decreases of diastolic AP (DAP) or vice versa were identified and the slope of the regression line in the (DAP,PR) plane was taken as an estimate of BR sensitivity (BRSprBR). The percentage of PR-DAP patterns (SEQ%prBR) was taken as a measure of prBR involvement and the prBR effectiveness index (EIprBR) was computed as the fraction of DAP sequences capable to drive antiparallel PR variations. Analogous markers were computed over cBR from HP and systolic AP (SAP) variability (i.e. BRScBR, SEQ%cBR and EIcBR). prBR and cBR were typified during incremental light-to-moderate bicycle ergometer exercise at 10%, 20% and 30% of the maximum effort in 16 healthy subjects (aged from 22 to 58 years, 6 males). We found that: i) BRScBR decreased gradually with the challenge, while BRSprBR declined only at the heaviest workload; ii) SEQ%cBR decreased solely at the lightest workload, while the decline of SEQ%prBR was significant regardless of the intensity of the challenge; iii) EIprBR and EIcBR were not affected by exercise; iv) after pooling together all the data regardless of the experimental conditions, BRSprBR and BRScBR were uncorrelated, while SEQ%cBR and SEQ%prBR as well as EIcBR and EIprBR, were significantly and positively correlated; v) when the correlation between SEQ%cBR and SEQ%prBR and between EIcBR and EIprBR was assessed separately in each experimental condition, it was not systematically detected. This study suggests that prBR characterization provides information complementary to cBR that might be fruitfully exploited to improve patients’ risk stratification.